Nutritional habits and the structure of consumption in the Kashubian population of the town of Jastarnia (the Hel Peninsula) - Budnik, Alicja (Anthropological Review, 1998)
The first part of the present study is a description of the Kashubian population inhabiting the Hel Peninsula. Further, the author follows the changes of the dietary pattern and the nutritional habits of this population over a span of more than one hundred years. The past nutritional habits (prevailing in the 18th century and in the first half of the 20th century) were reproduced on the basis of ethnographic source materials. The present day diet was determined on the basis of the data obtained by way of weekly family questionnaires and daily individual questionnaires distributed in September, June and November in Jastarnia among Kashubian families and school children. The results were then compared with the literature data and discussed.